Integration of Islam and Mathematics: Strengthening Technology Pedagogy Competence for Islamic Campus Students as Prospective Mathematics Teachers - Rizki Harahap; Ummi Rizqina Zahiroh Hr; Siti Ermaida Hasibuan (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This study aims to identify the impact of GeoGebra application training as a strategic effort to improve the technological pedagogical competence of Islamic campus students as prospective mathematics teachers at the Educational Personnel Training Institution. This program focuses on the knowledge, skills, and readiness of students in the Mathematics Education Study Program at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan in integrating GeoGebra into mathematics learning. The Participatory Action Research (PAR) approach is used. The results show that more than 80% of participants agreed that the training material is relevant, enhances understanding of GeoGebra concepts, and improves their practical teaching skills. Participants also rated the facilitators very highly in terms of mastery of the material and clarity of delivery. This research finding contributes to the affirmation that PAR-based training effectively enhances technological literacy and strengthens Technological Pedagogical Content Knowledge.